The calculation of some thermoelastic properties and pressure-temperature (P-T) diagrams of Rh and Sr using molecular dynamics simulation - Ciftci, Y. O.; Colakoglu, K.; Ozgen, S.; Kazanc, S. (Iop Publishing Ltd, 2007)
In this study, molecular dynamics simulations are carried out using a modified many-body Morse potential function in the framework of the embedded-atom method (EAM). Pressure-temperature (P-T) diagrams are determined for Rh and Sr. For the metals the bulk moduli are calculated from the pressure versus volume curves, and specific heats are calculated from the enthalpy versus temperature curves. The temperature and pressure dependence of the elastic constants and bulk moduli are also calculated for Rh and Sr. The obtained results are in good agreement with the available experimental data.
Keywords: Embedded-Atom Method; Mechanical-Properties; Elastic-Constants; Phase-Diagram; Fcc; Dependence; Metals; State; Transitions; Range